Dreambooks in the Middle Ages : A Global Perspective - Cappozzo, Valerio (Late Antiquity and Medieval Studies E-Books Online, Collection 2026, 2026)
This volume explores the intricate art of interpreting dream symbols by tracing the evolution of oneirocritical traditions across Asia, the Middle East, and the Latin West. Spanning the classical, medieval, and modern periods, it reveals how diverse cultures have used dreambooks to translate imagined realities into personal insight. A collection of scholarly essays, this volume vividly portrays humanity's enduring fascination with dreams as profound sources of knowledge-rooted in the past, experienced in the present, and foreshadowing the future. Also included is the "Conspectus of the Western Manuscripts and Early Printed Editions of the Somniale Danielis ," an essential reference for next generations of scholars. Contributors are Valerio Cappozzo, Gabriela Cerghedean, Lászlo Sándor Chardonnens, Lorenzo DiTommaso, Boyda Johnstone, Jesse Keskiaho, Pierre Lory, Bronwen Neil, Steven Oberhelman, Lotte Reinbold, and Brigid E. Vance.